Capacidade e sustentabilidade da gestão ambiental municipal: proposta de um sistema de indicadores e a avaliação do município de Angra dos Reis/ RJ - Toledo, Ricardo Abreu de (2009)
The environmental administration, here considered in a wide way and focused in the municipal extent, has it decentralization as part of the reformulation process of the Brazilian State. Some Brazilian states have been working in the decentralization process of the environmental administration, while others assumed more conservative postures, as the Rio de Janeiro State that, until the last government administration, opted for the displacement of the environmental administration. The lack of capacity of the municipal districts in environmental matter constitutes serious impediment to the decentralization of the environmental administration and the invigoration of the National System of Environment (SISNAMA). The analysis of the capacity and of the sustainability of the environmental administration of the municipal districts of the State of Rio de Janeiro in general and specially, the Municipal district of Angra dos Reis-RJ were the immediate objectives of research. The creation of a system of indicators of capacity of municipal environmental administration was as much an objective as a way or tool chosen with the intended of evaluate it and, this way, develop a system of numeric indicators was an option assumed just in the beginning of the work. As a result, it was verified that in 2002, the group of the State of Rio de Janeiro s municipal districts had, in relative terms, a larger general capacity of municipal environmental administration than the capacity, in general, of the others environmental administration group of municipal districts that constitute the municipal federations of the Southeast Area. However, that capacity was still low for the service of the "partner-environmental" demand for politics and environmental administration which was also measured by an own indicator development. That way, the work concludes that: (1) the late development that has been having in the transfer of attributions and environmental competences of the State of Rio de Janeiro to their municipal districts is due, probably, less to the absence of capacity of environmental administration in the municipal districts and more to other subjects related, for instance, to the expectation of loss of State powers and its dilution for the municipal districts, while, (2) by municipal districts, the late development in the autonomy search and construction of that capacity would involve disputes of power among responsible local sections of public politics administration, which don't want to have the initiatives of their actions judged by the environmental section; (3) the Municipal district of Angra dos Reis-RJ, in the 29th position of the ranking of the 92 State of Rio de Janeiro s municipal districts, with low capacity, in general, and low sustainability of environmental administration, didn't have the necessary conditions to assume more complex competences as, for instance, the environmental licensing. In the end of 2004 the Municipal district and the environmental section won an environment general office, but at the end of 2005 the municipal system of environment of Angra dos Reis-RJ still didn't have the capacity of environmental administration that it was compatible with its demand and institutional mission, for reasons that are shone subjectively in the present work.